Perkembangan Konsep Keadilan Distributif dalam Pemikiran Ekonomi Syariah: Tinjauan atas Doktrin Anti Monopoli - Asep Risnandar; Iib Hibaturohman; Nurrohman Syarif; Eko Bambang Rahmono; Tb Rifat (CV. Global Cendekia Inti, 2026)
Monopolistic practices and wealth distribution inequalities contradict the principle of justice in Islamic economics. This study aims to analyze the development of the concept of distributive justice and anti-monopoly doctrine in Islamic economic thought, as well as their relevance to competition regulation in Indonesia. The study employs a qualitative method with a historical-comparative approach through a literature review of the works of classical scholars and contemporary Muslim economists. Data were analyzed using content analysis and comparative analysis with Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition. The results show that the concept of distributive justice evolved from the normative foundations of the Qur’an and Sunnah into a comprehensive institutional framework. The Islamic anti-monopoly doctrine is built upon the prohibition of ihtikar, the hisbah mechanism, the concept of tas’ir, and the prohibition of market manipulation all grounded in the principles of ‘adl and the maqashid al-shari’ah. Although it has strong relevance to competition regulation in Indonesia, Law No. 5 of 1999 still requires strengthening of its ethical and moral dimensions, which are rooted in Islamic economic values. This study contributes to the development of a normative framework for Islamic economics as an alternative solution to monopolistic practices in Indonesia.